2021
DOI: 10.3389/fnins.2021.709684
|View full text |Cite
|
Sign up to set email alerts
|

Long Non-coding RNA T-uc.189 Modulates Neural Progenitor Cell Fate by Regulating Srsf3 During Mouse Cerebral Cortex Development

Abstract: Neurogenesis is a complex process that depends on the delicate regulation of spatial and temporal gene expression. In our previous study, we found that transcribed ultra-conserved regions (T-UCRs), a class of long non-coding RNAs that contain UCRs, are expressed in the developing nervous systems of mice, rhesus monkeys, and humans. In this study, we first detected the full-length sequence of T-uc.189, revealing that it was mainly concentrated in the ventricular zone (VZ) and that its expression decreased as th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 48 publications
0
3
0
Order By: Relevance
“…Another interesting regulatory mechanism exercised by T-UCRs was presented by Zhang et al [27]. The authors revealed a new regulatory relationship between T-UCRs and their host genes.…”
Section: Interaction Between T-ucrs and Mrnamentioning
confidence: 92%
See 1 more Smart Citation
“…Another interesting regulatory mechanism exercised by T-UCRs was presented by Zhang et al [27]. The authors revealed a new regulatory relationship between T-UCRs and their host genes.…”
Section: Interaction Between T-ucrs and Mrnamentioning
confidence: 92%
“…The authors revealed a new regulatory relationship between T-UCRs and their host genes. They suggested that uc.189 positively regulates the expression of the splicing factor SRp20, but did not provide any mechanistic evidence to explain how this occurs [27].…”
Section: Interaction Between T-ucrs and Mrnamentioning
confidence: 99%
“…It has been reported that the ucRNA, uc.189, promotes the development of the neocortex by limiting its expression to the ventricular zone (VZ) which is located in the nucleus. It was also identified the ucRNA, uc.189, can upregulate its regulatory target serine-arginine-rich splicing factor 3 (SRSF3) protein expression, which prevents the abnormal proliferation of neural progenitor cells [ 5 ]. E60UCS is important for brain development.…”
Section: Physiologymentioning
confidence: 99%